Youth Culture And Brand Preferences In South Africa - Motingoe, Tumelo (University of the Witwatersrand, Johannesburg, 2023)
The research study entitled Youth Culture and Brand Preferences was carried out to find out what are the cultural aspect from a socio-political perspective that drive youth cultural beliefs specifically within the Generation Z cohort. The study investigates Demography, Global Orientation, Local Orientation, Values and brand preference in two categories – Fashion and Alcohol. The study did this investigation using descriptive statistics and multinomial logistic regression as a tool to infer brand preference given the nominal brand choices that were put in play. In terms of marketing and management philosophy the study posits and develops on global consumer culture theory as a manner to which multinationals can strategize their entry or marketing activity into new markets specifically when looking at the generation Z consumer as the core target consumer
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Youth Culture; Brand Preferences; Socio-political perspective; UCTD; SDG-8: Decent work and economic growth